2020
DOI: 10.1093/ee/nvaa124
|View full text |Cite
|
Sign up to set email alerts
|

Life History and Rearing of Anastatus orientalis (Hymenoptera: Eupelmidae), an Egg Parasitoid of the Spotted Lanternfly (Hemiptera: Fulgoridae)

Abstract: To support efforts to manage and contain spotted lanternfly (SLF), Lycorma delicatula White (Hemiptera: Fulgoridae), research is being conducted to develop classical biological control methods. To date, two potential biocontrol agents from China have been identified: an egg parasitoid, Anastatus orientalis, and a nymphal parasitoid, Dryinus sinicus Olmi (Hymenoptera: Dryinidae). The research detailed here focuses on investigating the biology and rearing of A. orientalis to assess its potential efficacy in a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 23 publications
4
44
0
Order By: Relevance
“…Similarly, there was no significant difference in offspring emergence in A. bifasciatus parasitizing H. halys eggs stored in a −80 • C freezer for up to 24 months [9]. Broadley et al [11] reported that field-collected spotted lanternfly eggs stored at 5 • C for 10 months did not affect the progeny production, parasitism rate, and female ratio of A. orientalis. Similar results were reported by Alim and Lim [22,23] with eggs of Riptortus pedestris Fabricius stored at 2 • C for parasitism by Gryon japonicum Ashmead, and Ooencyrtus nezarae Ishii and by Peverieri et al [36] with eggs of Leptoglossus occidentalis Heidemann stored at 4 • C for parasitism by Gryon pennsylvanicum Ashmead.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, there was no significant difference in offspring emergence in A. bifasciatus parasitizing H. halys eggs stored in a −80 • C freezer for up to 24 months [9]. Broadley et al [11] reported that field-collected spotted lanternfly eggs stored at 5 • C for 10 months did not affect the progeny production, parasitism rate, and female ratio of A. orientalis. Similar results were reported by Alim and Lim [22,23] with eggs of Riptortus pedestris Fabricius stored at 2 • C for parasitism by Gryon japonicum Ashmead, and Ooencyrtus nezarae Ishii and by Peverieri et al [36] with eggs of Leptoglossus occidentalis Heidemann stored at 4 • C for parasitism by Gryon pennsylvanicum Ashmead.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies on Anastatus spp. have mentioned cold storage of host eggs and its possible effect on Anastatus fitness, but the most effective methods for host egg storage have not been reported [7,9,11,12]. Parasitoids reared on refrigerated eggs may have reduced fitness, because long-term cold storage of host eggs can decrease their quality [10,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the carrier of sperm may be lost in the maternal line. The more significant the toxicity of indoxacarb is, the greater the carrier loss and the number of fertilized eggs decreased [ 37 ]. Therefore, the ratio of female offspring decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the proactive biological control program underway in California targeting L. delicatula has focused research efforts on A. orientalis. Broadley et al (18) investigated aspects of the biology and rearing of A. orientalis. One finding from this study was that the number and sex ratio of progeny produced and parasitism rates of A. orientalis per L. delicatula egg mass did not differ between newly collected eggs vs. eggs stored at 5°C for up to 10 months.…”
Section: Introductionmentioning
confidence: 99%